Efektifitas perlakuan awal Tretinoin 0,1% Topikal pada Proses Penyembuhan di Luka Insisi pada Mencit (Mus musculus) - Iswinarno Doso Saputro; Hesty Aulia Palupi; Wiwik Misaco Yuniarti (Jurnal Sain Veteriner, 2018)
Tretinoin has an important role in wound healing process include improve fibroplasia and collagen synthesis, maintening humoral immunity, and neutralize steroid effect.Epithelization  and fibroblast proliferation were very important event in wound healing process. The aims of this study were studying epithelization and fibroblas proliferation on incision wound healing process using pre treatment of  Tretinoin 0,1%  topically on mice. This research used 24 male mice, 3 month of age, with 150 -180 gram of body weight. The mice were divided into 2 groups, control group (K) and treatment group (P). The control group was a group of mice with an incision wound, while the treatment group was a group of mice with an incision wound that received a pretreatment of Tretionin of 0.1% topically. Each group was divided into 2 sub groups K4, K7, P4, P7 based on time of samples collecting. K4 and P4 were examined at  day 4, while K7 and P7 were examined at day 7. Epithelialization was observed by measuring the length of the epithelial incision area, whereas fibroblast proliferation was performed by counting the number of fibroblasts in five field of view on histopathologic skin preparations processed by HE staining.In this study,pretreatment of Tretinoin 0,1%  topically can increase epithelialization and number of fibroblast significantly (p<0,05).This increase may be due to 1% Tretinoin in the tissues to induce keratinocyte basal proliferation including its migration to the skin surface via retinoic acid receptors ( RARδ)Pretreatment of Tretinoin 0,1% topically can increased epithelialization and number of fibroblast on incision wound healing process of albino rats